MOLECULAR PHYLOGENY OF RODENTIA DERIVED FROM NRAS GENE SEQUENCES - Yudi Gebri Foenna; Hartono Hartono; Imelda Maelani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Rodentia is the most diverse mammalian order, yet phylogenetic relationships among several rodent lineages remain incompletely resolved, particularly when inferred predominantly from mitochondrial markers. This study aims to assess the potential of the nuclear NRAS (Neuroblastoma RAS viral oncogene homolog) gene for reconstructing rodent phylogeny. A total of 18 NRAS nucleotide sequences representing major rodent families were retrieved from the NCBI GenBank database, with Equus caballus and Oryctolagus cuniculus used as outgroups. Sequence alignment and model selection were performed using MEGA 12 under Maximum Likelihood criteria. Phylogenetic reconstruction was conducted using the Maximum Likelihood method with the T92+G+I substitution model and 1,000 bootstrap replicates. Pairwise genetic distances were estimated using the p-distance method and visualized through a heatmap to examine divergence patterns. The results indicated that NRAS evolution is best explained by models incorporating invariant sites and rate heterogeneity, reflecting strong functional constraints combined with lineage-specific variation. The inferred phylogeny is largely congruent with established rodent systematics, and genetic distance patterns independently support the recovered topology. These findings suggest that NRAS represents a reliable nuclear marker that offers complementary phylogenetic information alongside mitochondrial data in Rodentia phylogenetic studies.